2011
DOI: 10.1007/s00027-011-0218-3
|View full text |Cite
|
Sign up to set email alerts
|

Do seasonal changes in habitat features influence aquatic macroinvertebrate assemblages in perennial versus temporary Mediterranean streams?

Abstract: In this study we examined the importance of seasonal changes in habitat features and aquatic macroinvertebrate responses in temporary and perennial streams from two different catchments in the Western Mediterranean region in Spain. Macroinvertebrate sampling was spatially intensive to account for the relative frequency of meso-(i.e., riffles and pools) and micro-habitats (i.e., different mineral and organic-based substrata) at each site. Samples were collected at two distinctly different phases of the hydrogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 62 publications
(72 reference statements)
8
43
0
2
Order By: Relevance
“…Initial floods following wildfires enhance runoff and erosion rates in burned terrains, causing elevated sediment and phosphorus concentrations in receiving downstream water bodies (Blake et al, 2010). Finally, studies that focused on the relative vulnerability of PRS and NPRS to anthropogenic stress have shown that habitat changes (García-Roger et al, 2011) and agro-industrial pressures ) exert severe effects on aquatic macroinvertebrates in NPRS, more severe than in comparable PRS.…”
Section: Pressures and Impactsmentioning
confidence: 99%
“…Initial floods following wildfires enhance runoff and erosion rates in burned terrains, causing elevated sediment and phosphorus concentrations in receiving downstream water bodies (Blake et al, 2010). Finally, studies that focused on the relative vulnerability of PRS and NPRS to anthropogenic stress have shown that habitat changes (García-Roger et al, 2011) and agro-industrial pressures ) exert severe effects on aquatic macroinvertebrates in NPRS, more severe than in comparable PRS.…”
Section: Pressures and Impactsmentioning
confidence: 99%
“…These systems experience excessive water abstraction and their intermittency can be considered primarily artificial. Garcia-Roger et al (2011) studied aquatic macroinvertebrates in several temporary rivers and related temporal changes in the physical habitat to changes in community structure. They quantified and characterised the physical habitat at local (substrata), reach (riffle and pools), and catchment (among streams) scales and found that changes in substrata availability and riffle-pool sequences had an overriding influence on spatial variability in macroinvertebrate assemblages.…”
Section: Scope Of the Special Issuementioning
confidence: 99%
“…For example, of the different refuge possibilities for aquatic taxa during drying (e.g., hyporheic zone, remnant pools, adjacent ponds, moist organic substrate) what types of conditions are necessary for various species to adequately resist the lethal nature of drying (e.g., see Garcia-Roger et al 2011;Hodges and Magoulick 2011;Stubbington et al 2011)? Conversely, what habitat components of the dry riverbed support the diversity of terrestrial taxa (invertebrates, amphibians, mammals, birds)?…”
Section: Research Perspectives: Gaps and Needs In Temporary River Ecomentioning
confidence: 99%
“…In aquatic ecosystems, the prolonged dry season leads to reduced summer streamflow, which causes a shift in ecosystem composition from organisms that are well-suited to lotic (i.e., flowing) environments to those well suited to lentic (non-flowing) ones [23,24]. Interannual variability of climate can produce varying flow conditions by the conclusion of the dry season (either flowing or intermittent), which can also cause differences in community composition and structure from one year to the next [25,26]. Spatial analyses have suggested that the distribution of areas having Mediterranean climate characteristics will change with changing global climate dynamics [15], and the persistence of Mediterranean-climate ecosystems are at risk from the increased variability and shifts in precipitation and temperature patterns expected with climate change [27,28].…”
Section: Introductionmentioning
confidence: 99%